SOLUSI ANALITIK PENYEBARAN SEDIMEN PADA PERAIRAN TIDAK BERARUS DAN SALURAN ANULAR - Irfan Sitanggang (NIM 25097069), Khairil
Abstract : Sediment transport equation may be solved numerically using various methods, such as finite difference, finite element, etc. These solutions are subject to error which depends on many factors. The accuracy of the method must be assessed in order the solution to be considered valid. Two analytical solutions, namely the sediment deposition process at "no-current" water body and sediment transport at anular channel are pre-sented. Both are affected by the advection and diffusion type processes. These solutions can be used as a numerical model test. Using them, several numerical solutions of sediment transport equation, i.e. the FTCS, Upwind, Leonard and Crank Nicolson finite difference method, including the LAPI-ITB numerical model, were examined.